A genetically defined asymmetry underlies the inhibitory control of flexor–extensor locomotor movements - Britz, Olivier (eLife, 2015)
V1 and V2b interneurons (INs) are essential for the production of an alternating flexor–extensor motor output. Using a tripartite genetic system to selectively ablate either V1 or V2b INs in the caudal spinal cord and assess their specific functions in awake behaving animals, we find that V1 and V2b INs function in an opposing manner to control flexor–extensor-driven movements. Ablation of V1 INs results in limb hyperflexion, suggesting that V1 IN-derived inhibition is needed for proper extension movements of the limb. The loss of V2b INs results in hindlimb hyperextension and a delay in the transition from stance phase to swing phase, demonstrating V2b INs are required for the timely initiation and execution of limb flexion movements. Our findings also reveal a bias in the innervation of flexor- and extensor-related motor neurons by V1 and V2b INs that likely contributes to their differential actions on flexion–extension movements. DOI: http://dx.doi.org/10.7554/eLife.04718.001